Interaction between Notch signaling pathway and bioactive compounds and its intervention on cancer - Nie, Rong-Zu; Wang, Hang; Wang, Shuang-Shuang; Luo, Huo-Min; Chen, Chen; Jing, Zhao-Hui; Li, Pei-Feng (Frontiers in Nutrition, 2025)
The Notch signaling pathway is pivotal in cancer regulation, with its effects varying based on activation degree, tissue origin, and microenvironment. The dual role of Notch signaling is significant. It can promote or inhibit cancer progression depending on the context. This duality emphasizes the importance of nuanced therapeutic approaches. Recent research highlights natural bioactive compounds as modulators of Notch signaling, providing innovative insights for cancer prevention and therapy. This review explores the structural and functional mechanisms of Notch signaling in carcinogenesis and examines how natural compounds influence its activity, offering a foundation for targeted treatments. Bioactive compounds, such as flavonoids, non-flavonoids polyphenols, and terpenoids, show potential in modulating Notch signaling with low toxicity and multi-target effects. Compounds like resveratrol, curcumin, and EGCG inhibit key nodes in Notch signaling, reducing cancer cell proliferation and inflammation. Despite its promise, targeting Notch signaling poses challenges due to its complexity and variability across different cancers. Future research should focus on understanding the tissue-specific effects of Notch signaling, optimizing bioactive compound structures, and integrating basic and clinical studies to develop precision therapies. This review underscores the intricate role of Notch signaling in cancer and the transformative potential of bioactive compounds in therapeutic interventions.